THE INTERRELATION OF POPULATION SAVINGS AND INVESTMENTS UNDER CRISIS CONDITIONS - E. Tutukina; N. Timofeeva (Управленческие науки)
The mechanism of transformation of savings into investments consolidates scattered household savings and turns them into an important source of investment. Transforming savings into tangible, intangible and financial assets, population increases it is own wealth. The population involved in the investment process through their savings, is increasingly becoming personally involved in socio-economic development of the country, reaping the results at the same time.The relevance of the problem lies in the fact that savings of the population that can be transformed into investment are the major factor in accumulation of internal reserves for stimulating economic growth and modernization of the Russian economy.There is undulation in the dynamics of savings due to the influence of the economic cycle. Proceeding from this in this article the following hypothesis were put forward:the existence of regularities in the population’s savings behavior at different stages of the economic cycle;the economic crisis affects the amount and structure of savings regardless of the nature of occurrence of the crisis. To prove the hypotheses written above the analysis of data over the period of 1997-2013 was conducted.The analysis includes the following steps: defining subjects of savings; descripting the concepts of savings and investments; identifying the relationship between savings and investment; analyzing the savings behavior and motives of savings at pre-crisis stage; in time of crisis, as well as at the stage of economic recovery; calculating share of each form of savings in structure of total household savings; calculating the volume of savings and investment at different stages of economic cycles; identifying the relationship between the real disposable income, the level of consumption, investment and savings at different stages of economic cycles.The following analysis will allow to conclude on the preferred forms of savings from the population, as well as will help to determine the quality of which public institutions should be developed to stimulate the investment activity of the population.